Facial dysplasia in wild chimpanzees. Issue 4 (22nd May 2014) - Krief, Sabrina; Krief, Jean‐Michel; Seguya, Andrew; Couly, Gérard; Levi, Giovanni
Abstract At least 10% of the Sebitoli chimpanzee community of the Kibale National Park (Uganda) present a characteristic facial phenotype with flattened nose, reduced nostrils, and concave mid‐face. Affected individuals do not present skin lesions, and also young infants are affected. We suggest, therefore, a congenital origin of this defect.